2016
DOI: 10.1177/0300060515598902
|View full text |Cite
|
Sign up to set email alerts
|

Salivary interleukin-1β: Oral inflammatory biomarker in patients with psoriasis

Abstract: ObjectiveTo evaluate salivary interleukin (IL)-1β levels in patients with psoriasis, before and after treatment with tumour necrosis factor (TNF)-α inhibitors.MethodsIn this pilot study, salivary secretions were collected from patients with psoriasis and untreated healthy control subjects at baseline, and from patients after 12 weeks’ treatment with TNF-α inhibitors. IL-1β levels were determined in saliva samples via enzyme-linked immunosorbent assays, undertaken before and after TNF-α inhibitor treatment. Pso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
1
5
0
2
Order By: Relevance
“…The studies had been Dermatology Review/Przegląd Dermatologiczny 2021/2 published from 1973 to 2016. Two studies were reported from England [18,19], 2 from Italy [20,21], two from Germany [22,23], and 1 from each of the following countries: France [24], Finland [25], Japan [26], Israel [27], Bulgaria [28], Syria [29], the Netherlands [30], and Iran [6].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies had been Dermatology Review/Przegląd Dermatologiczny 2021/2 published from 1973 to 2016. Two studies were reported from England [18,19], 2 from Italy [20,21], two from Germany [22,23], and 1 from each of the following countries: France [24], Finland [25], Japan [26], Israel [27], Bulgaria [28], Syria [29], the Netherlands [30], and Iran [6].…”
Section: Resultsmentioning
confidence: 99%
“…Prace zostały opublikowane od 1973 do 2016 roku. Zbiór obejmował po dwa badania z Wielkiej Brytanii [18,19], Włoch [20,21] i Niemiec [22,23] oraz po jednym z Francji [24], Finlandii [25], Japonii [26], Izraela [27], Bułgarii [28], Syrii [29], Holandii [30] i Iranu [6]. stężenia α-amylazy, kortyzolu, igA i interleukiny 1b w ślinie Analizę zbiorczą stężeń α-amylazy, kortyzolu, IgA i interleukiny 1b w ślinie przedstawiono na rycinie 2.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Furthermore, the association between psoriasis and oral mucosa could be indicated by the increased salivary [ 27 ] and serum levels of TGF- β 1 and MCP-1 in psoriasis patients [ 39 , 40 ]. In a different investigation, Ganzetti and coworkers confirmed the validity of saliva as a noninvasive tool to monitor inflammation in psoriasis [ 41 ]. At baseline, psoriasis patients had higher salivary levels of IL-1 β , evaluated via an enzyme-linked immunosorbent assay (ELISA), in comparison to healthy individuals.…”
Section: Saliva and Correlated Biomarkers In Psoriasismentioning
confidence: 99%